Comparative study of the renoprotective effects of captopril and aminophylline against cainst cisplatin – induced nephrotoxicty in rats - .Sheeh, *Adel .H (AL-Kindy College Medical Journal, 2010)
Background: Cisplatin is one of the mostcommonly used anti-cancer drugs , but itsclinical use was limited by its nephrotoxicity .Methods: In this study we try to investigate therenoprotective effect of captopril andaminophylline against cisplatin inducednephrotoxicity .For this purpose a 36 SpragueDawley rats was divided randomly to 6 groups ,each group consist of 6 rats. The first groupgiven normal saline and act as control group,while the other 5 groups given cisplatin ( 7.5mg/kg ) , captopril ( 60 mg/kg ) , aminophylline( 24 mg/kg ) , captopril with cisplatin andaminophylline with cisplatin respectively. Alldrugs are given as single dose throughintraperitonial route. After 6 days blood ureaand serum creatinine, malondialdehyde andglutathione are measured and compared withcontrol group.Results: The data show that both captopril andaminophylline posses renoprotective effectagainst cisplatin – induced nephrotoxicity, alsothe data show that captopril renoprotectiveeffect is more than that produced byaminophylline.Conclusions: This data can help in increase thedose of cisplatin in clinical uses together withuse of renoprotective agent , specially if thepatient already need such renoprotective drugsfor treatment of disease a way from cisplatin ashypertension .Also more clinical studiesrequired for more assessment of the clinicalpattern of this renoprotective effect